Takhrij and Syarah Hadith of Agrotechnology Benefits of Using Siwak - Mohammad Fajar Septian; Wahyudin Darmalaksana; Mi'raj Fuadi (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the benefits of using miswak. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this research are the benefits of using siwak according to scientific research. The conclusion of the research is takhrij and syarah hadith of the Prophet. About the siwak plant with agrotechnology analysis shows many benefits, especially in the health sector.